Critical risk factors of joint venture projects in the oil and gas industry - Fatemeh Baradari; Zulkifli Mohd Nopiah; Sabirin Ja’afar; Wan Siti Adibah Wan Dahlan (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Oil and Gas (O&G) industry is one of the riskiest, most dynamic and challenging industries and plays a vital role in every nation’s economy. Like any other major industry, O&G is exposed to a host of both predictable and unpredictable risks. Joint venture projects (JVP) are often regarded as a risky business as there is a high failure rate among them because of the complexities involved. This paper aims to identify the critical risk factors (CRFs) of JVPs for O&G between Malaysia and Thailand. Via systematic literature review (SLR) the risk factors for O&G and JVPs around the globe are identified and a set of questions relating to them were designed and used in a pilot study. A total of 15 respondents from different background experiences working in O&G JVPs were requested to answer the designed questionnaire during the pilot study. The questionnaire survey passed the required Cronbach Alpha value of 0.6 with a score of 0.98. The data collected involved 170 respondents currently working or have worked in O&G JVPs. The relative importance index (RII) for each risk factor’s (RF) value was quantified and the RFs ranked based on the value. A RII value exceeding 60% is considered to have agreement and of importance to the respondents. The RII value can be used as an indicator to rank the RFs from the most to the least critical. The CRF categories determined in this study are environmental, cultural and social, and organisation. Under environmental, the main CRFs are losses due to fluctuations in exchange rates/interest rates. For cultural and social, the main CRFs are problems associated with cultural differences and cooperation. Organisational issues related to organisational fit, incompetent project management team, difficulty in finding and keeping skilled workers, and low worker productivity. All the listed RFs underwent a comprehensive study on their impact and probability of occurrence to determine the best processes, methods, and tools for managing the risks. It is recommended that key players in the O&G industry consider all the RFs of JVPs during the risk management evaluation stage.